Penyuluhan Anti Bullying terhadap Karang Taruna “Bintang Timoer” Dusun Jetak dalam Menciptakan Kondisi Masyarakat yang Harmonis - Sutarto, Retno Eko Mardani; Aisyah Rukmi Widowati; Siti Fatimah; Aziz Widhi Nugroho; Azahery Insan Kamil; Aisyania Yogi Puspita; Siti Nurjanna Lessy; Rengga Kusuma Putra (Pusat Riset dan Inovasi Nasional, 2026)
Violence and bullying are social issues that still frequently arise among adolescents, both in schools and communities. Lack of knowledge about the forms, impacts, and prevention mechanisms of bullying means that such behavior is often considered normal and not immediately addressed. This community service activity aims to increase the understanding and awareness of adolescents, especially in the Karang Taruna